Real‐world treatment patterns and outcomes in non‐transplant newly diagnosed multiple Myeloma in France, Germany, Italy, and the United Kingdom. (9th June 2020) - Mohty, Mohamad; Knauf, Wolfgang; Romanus, Dorothy; Corman, Shelby; Verleger, Katharina; Kwon, Youngmin; Cherepanov, Dasha; Cambron‐Mellott, M. Janelle; Vikis, Haris G.; Gonzalez, Francisco; Gavini, Francois; Ramasamy, Karthik
Abstract: Objectives: The treatment paradigm in newly diagnosed multiple myeloma (NDMM) is evolving toward individualized, risk‐directed, and longer duration of therapy (DOT). The objective of this study was to describe treatment patterns and outcomes in non‐transplant NDMM in four European countries. Methods: This retrospective chart review included adults with NDMM diagnosed between January 1, 2012, and December 31, 2013 (early cohort), or April 1, 2016, and March 31, 2017 (recent cohort). Results: Among 836 patients, molecular testing was performed in 21% and 35% patients of early vs recent cohorts; proteasome inhibitor (PI)/alkylator combinations were the principal first‐line (1 L) therapy (39% vs 43%). Use of immunomodulatory drug (IMID)/alkylator combinations declined from early to recent cohort (26% vs 13%) but IMID (7% vs 16%) use increased. Few patients (5%) received 1 L maintenance therapy. Two‐thirds of patients were treated with a fixed duration intent, with a median 7‐month 1 L DOT and progression‐free survival (PFS) of 32.8 months in the early cohort. Both 1 L DOT and PFS were longer with oral compared to injectable regimens. Conclusions: Although frontline treatment patterns changed significantly, 1 L DOT is short. The uptake of molecular testing and 1 L maintenance is low. These results highlight areas of unmet need in NDMM.